Shrouded: Islam, War, and Holy War in Southeast Asia - Barter, Shane J. ca. 20./21. Jh. (Journal for the scientific study of religion, 2014)
The relationship between Islam and war has been the focus of lively debates. While terrorism experts might find a holy war wherever they look, others deny the role of faith in motivating violence. While no conflict is entirely inspired by faith, nor is any conflict entirely without it, the degree of religious motivation matters a great deal. How does one gauge the religiosity of a given conflict? We identify three dominant approaches: citing scripture, citing militant leaders, and quantifying religious divisions. While each approach makes valuable contributions, none help us to understand the degree to which a given struggle is understood by Muslim communities to be sacred. Based on rural fieldwork in three Southeast Asian secessionist conflicts, this article provides a series of empirical indicators of religious conflict: the religious credentials of rebel leaders, recruitment networks, public discourse, and burial practices. Burial practices for fallen rebels provide especially novel insights into how conflicts are understood by local religious officials and Muslim communities, offering a new window into understanding religiosity as perceived by internal audiences.